Benefits of budesonide/glycopyrrolate/formoterol fumarate (BGF) on symptoms and quality of life in patients with COPD in the ETHOS trial. (August 2021) - Martinez, Fernando J.; Rabe, Klaus F.; Ferguson, Gary T.; Wedzicha, Jadwiga A.; Trivedi, Roopa; Jenkins, Martin; Darken, Patrick; Aurivillius, Magnus; Dorinsky, Paul
Abstract: Background: We report the long-term effects of triple therapy with budesonide/glycopyrrolate/formoterol fumarate (BGF) vs glycopyrrolate/formoterol fumarate (GFF) and budesonide/formoterol fumarate (BFF) on symptoms and health-related quality of life (HRQoL) over 52 weeks in the Phase III ETHOS study of patients with moderate-to-very severe COPD. Methods: ETHOS was a randomized, double-blind, multi-center, parallel-group study in symptomatic patients with COPD who experienced ≥1 moderate/severe exacerbation in the previous year. Patients received twice-daily BGF 320/18/9.6 μg, BGF 160/18/9.6 μg, GFF 18/9.6 μg, or BFF 320/9.6 μg, administered via a single Aerosphere inhaler, for 52 weeks. Results: The modified intent-to-treat population included 8509 patients (mean age 64.7 years; 59.7% male; mean COPD Assessment Test score, 19.6). BGF significantly reduced rescue medication use vs GFF and BFF (−0.53 puffs/day [p < 0.0001] and −0.35 puffs/day [p = 0.0002], respectively, with BGF 320 over 52 weeks). BGF 320 also significantly improved St George's Respiratory Questionnaire (SGRQ) total score over 24 and 52 weeks vs dual therapies, resulting in the greatest proportion of SGRQ responders vs dual therapies over 24 weeks (52.5% vs 42.5% [GFF] and 45.2% [BFF]) and 52 weeks (47.0% vs 37.8% [GFF] and 41.0% [BFF]). Similar results were observed with BGF 160. Benefits were also observed vs dual therapies in symptomatic endpoints including Transition Dyspnea Index focal score, EXAcerbations of Chronic pulmonary disease Tool total scores and Evaluating Respiratory Symptoms in COPD total scores over 24 and 52 weeks. Conclusions: BGF triple therapy improved symptoms and HRQoL vs dual therapies over 24 and 52 weeks in patients with moderate-to-very severe COPD. Highlights: BGF 320 demonstrated symptoms & HRQoL benefits vs dual therapies over 24 & 52 weeks. BGF 160 also demonstrated benefits for symptoms and HRQoL vs dual therapies. Benefits for symptoms and QoL with BGF 320 were sustained over 52 weeks.